A Low Cost Antibody Signal Enhancer Improves Immunolabeling in Cell Culture, Primate Brain and Human Cancer Biopsy. (15th July 2020) - Flores-Maldonado, Catalina; Albino-Sánchez, M. Estela; Rodríguez-Callejas, Juan D.; Estrada-Mondragon, Argel; León-Galicia, Ismael; Maqueda-Alfaro, Raúl; Perez-Cruz, Claudia; Fuchs, Eberhard; García-Carrancá, Alejandro; Contreras, Rubén G.; Missirlis, Fanis; Rosas-Arellano, Abraham
Highlights: ASE significantly improves immunofluorescence in brain primate tissue. ASE is also effective for cell culture immunocytofluorescence. ASE does not alter the location and/or distribution of immunolabeling. ASE increases the intensity of immunolocalization of cancer biomarkers. ASE is a cost-friendly alternative to clinical protocols that use commercial enhancers. Abstract: The use of antibodies to identify neuronal receptors, neurotransmitters, cytoskeletal elements or pathologic protein aggregates, ion channels, adhesion molecules or other cell-type specific markers, is common practice in neuroscience. Antibody detection systems are often based on confocal, epifluorescence or brightfield microscopy. Three types of technical issues can interfere with immunolabeling: low abundance of the target protein, low specific affinity of the antibody and/or signal background sometimes related to tissue fixation. Here, giving tribute to Professor Miledi's mentorship, we propose the application of an antibody signal enhancer (ASE) solution based on glycine, hydrogen peroxide and a detergent mix as a simple, low cost, protocol variation that significantly and specifically improves the signal to noise ratio during immunostaining experiments. We describe three new settings in which ASE improves the detection of a variety of antibodies applied on long-time stored non-human primate brain sections, cell culture monolayers and on squamous carcinomas retrieved from cervical cancer patients. The significant improvement of ASE over optimized immunohistochemical protocols used in clinical practice (i.e. cancer detection) combined with its simplicity and low cost makes it an attractive method for biomedical applications.